2015 6th International Conference on Information, Intelligence, Systems and Applications (IISA) 2015
DOI: 10.1109/iisa.2015.7387988
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of edge-less and edge-based approaches for horizon line detection

Abstract: Abstract-Horizon line detection requires finding a boundary which segments an image into sky and non-sky regions. It has many applications including visual geo-localization and geotagging, robot navigation/localization, and ship detection and port security. Recently, two machine learning based approaches have been proposed for horizon line detection: one relying on edge classification and the other relying on pixel classification. In the edge-based approach, a classifier is used to refine the edge map by remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…It contains modern photographs of mountainous terrain including challenging situations like cloud occlusions, low contrast horizons, and images taken from within cable cars (Figure 5). The dataset was used by a wide range of authors (e.g., [16,31]) for evaluation. While it consists of color images, for the developed method, the grayscale images are derived by averaging the color channels.…”
Section: Ch1mentioning
confidence: 99%
“…It contains modern photographs of mountainous terrain including challenging situations like cloud occlusions, low contrast horizons, and images taken from within cable cars (Figure 5). The dataset was used by a wide range of authors (e.g., [16,31]) for evaluation. While it consists of color images, for the developed method, the grayscale images are derived by averaging the color channels.…”
Section: Ch1mentioning
confidence: 99%
“…is mostly not answered. This is true with the exception of few [2], [27], [28], [1], [29] who have reported such measures. For example; Saurer et al [15] reported full automatic detection for 60% of their images (total 948), however how good the detections were for these images was never mentioned.…”
Section: B Paper Contributionmentioning
confidence: 99%
“…The body of work on truly automatic non-linear horizon/sky line detection is rather limited and work comparing such methods is even rarer with the exception of Ahmad et al who compare different formulation [26], [27], [28] of their approach against original approach of [4]. And quite recently the work by Porzi et al [29]; who proposed a small scale deeplearning architecture inspired from VGG [31] for horizon line detection.…”
Section: B Paper Contributionmentioning
confidence: 99%
“…Due to the unavailability of catadioptric mirrors, the authors manually synthesize the catadioptric images. Ahmad et al 7 present a detailed comparison between two machine learning-based approaches for horizon line detection (edge and edgeless-based). Additionally, they propose a fusion strategy, combining both approaches for better results, but they fail to provide attitude estimations using the detected horizon.…”
Section: Introduction and Related Workmentioning
confidence: 99%